Management System Including Health Care and Marketing of Pigs Adopted by Farmers in Dhankuta and Terhathum Districts - Sah, R.P.; Jha, S.K.; Karki, S. (Nepalese Veterinary Journal, 2018)
Study was carried out to explore the management system of pig including health care and marketing, adopted by farmers in Hattikharka of Dhankuta and Phakchamara of Terhathum districts. A semi-structured questionnaire was distributed to a total of 200 pig farmers of selected sites. Farmers were surveyed to acquire information on management systems of pig such as, housing, breeding, feeding, health care and marketing. Majority of pig farmers kept Pakhribas black pig, chawanche and their crosses. Population of local pigs was found three times more than improved breeds in both sites. Generally, 1-5 pigs were raised by a farmer. Bamboo, wood and mud were mostly used as housing material. Stall feeding system was adopted by most of the farmers. Locally available feeding materials such as, rice bran, rice polish, maize, sisno, karklo, swill feeding, leftover food and green grasses like rayo, latte sag, kande jhar, twigs of fodder, khubhindo, pumpkin etc were mostly used for pig. Rai, Sherpa, Tamang, Gurung, Limbu, Magar, BK and Shrestha communities were mainly rearing pigs. Diarrhea, gastroenteritis, piglet mortality, agalactia, repeat breeding, parasitic infestation, etc were reported as the common diseases in pigs. Drenching against worm was adopted by few farmers and drugs like albendazole and fenbendazole were common. Vaccination against swine fever was also reported by the farmers and is in increasing trend as a preventive measure. According to farmers, demand for pigs is more than supply in the market and all the pigs are marketed and consumed within the district.